Facial Skin Injury Related to Personal Protective Equipment Among Healthcare Workers: Single Center Cross-Sectional Study - I Gusti Ayu Agung Bella Jayaningrum; Gede Benny Setia Wirawan; Anak Agung Ngurah Krisna Dwipayana; Anak Agung Ngurah Bagus Surya Darma; Lya Lusyana; Sang Nyoman Suriana (DiscoverSys Inc., 2021)
Objective: Our study aimed to learn the phenomenon of facial skin injuries related to PPE use, their characteristics, as well as risk and protective factors.Methods: We conducted a single-center cross-sectional study. Samples was collected consecutively by disseminating self-filled questionnaire to all departments in Sanjiwani General Hospital, Gianyar, Bali, Indonesia. Variables studied included demographic, characteristics of PPE usage, characteristics of facial skin injuries suffered, and preventive measures practiced by healthcare workers. We conducted multivariate analysis for independent determinants of more severe skin injuries and any injuries located on the nasal bridge, cheekbones, and behind the ears.Results: Final analysis included 161 respondents. Male make up 26.7% of respondents, mean age was 35.00 (± 8.91). The majority was nurses (78.3%). Prevalence of skin injury was 90.7%, 39.1% of them being partial or full thickness skin injuries. Only 27.4% respondents practiced preventive measures, including application of polyester tape layering and emollient. The most frequently reported location of skin injury was nasal bridge (77%), followed by behind the ears (57.1%), and on the cheekbones (47.2%). Multivariate analyses discovered that KN95 respirator poses less risk for more severe injuries compared to N95. Protective measures were found effective to prevent skin injuries in all locations, including for more severe injuries.Conclusions: We found high prevalence of facial skin injuries among healthcare workers accompanied by inadequate practice of preventive behaviors. These preventive behaviors have been found effective in other study as well and existing evidence support its promotion for more widespread practice.